Early arrivals: association of maternal obstetric factors with preterm births and their survival in India. (October 2022) - Jana, A.; Banerjee, K.; Khan, P.K.
Abstract: Objectives: Preterm birth (PTB) increases the risk of various acute and chronic morbidities and premature mortality in children under 5 years of age. The present study examines the association between different maternal obstetric factors and PTB. In addition, this study estimates the risk of neonatal mortality among children born preterm. Study design: Retrospective two-stage stratified sample design. Methods: The weighted prevalence of PTB was estimated using data on 148, 746 most recent institutional births from the National Family Health Survey (NFHS)-4, 2015–16. The Poisson regression model was used to investigate the association between maternal obstetric factors and PTB. Using Cox's proportional hazard model, the risk of neonatal mortality among PTBs was estimated. Results: Maternal obstetric factors, such as minimal antenatal care, delivery complications, history of previous caesarean delivery and delivery at private health facilities, were significantly associated with an increased risk of PTB. The survival probability of preterm babies sharply declined in the first week of life and thereafter was found to stabilise. The risk of mortality in the first 28 days of life increased 2.5-fold if the baby was born preterm. Optimising antenatal care was found to lower the likelihood of PTB and improve their chances of survival. Conclusion: Antenatal care services and delivery care practices in private facilities were strongly associated with the incidence and survival of PTB. Evaluating associations of history of caesarean births on future pregnancies can help understand their deleterious effects on PTB. Affordable, accessible and available antenatal care services, in both public and private facilities, can increase the survival rates of PTBs.